Pengaruh Promosi Media Sosial, Endorsement, Dan Harga Terhadap Keputusan Pembelian (Studi Pada Produk Fashion H&M Di Beachwalk Kuta, Bali) - Ni Putu Desy Natalia; Luh Komang Candra Dewi (Journal Research of Management, 2025)
Purchase decisions are the process by which consumers determine and implement their choices regarding a product or service. This study aims to determine the influence of social media promotions, endorsements, and price on purchasing decisions for H&M fashion products. This quantitative study employed a survey method. The population was H&M consumers who had previously purchased H&M products and were at least 17 years old. Purposive sampling was used, with 90 respondents. Data analysis methods used included validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test. The results of the multiple linear regression analysis showed a regression model of Y = 1.503 + 0.226 X1 + 0.273 X2 + 0.506 X3. The conclusion is that social media promotions have a positive and significant effect on purchasing decisions, as indicated by a positive regression coefficient of 0.226 and a significance level of 0.020 <0.05. Endorsement has a positive and significant effect on purchasing decisions, as indicated by a positive regression coefficient of 0.273 and a significance level of 0.005 < 0.05. Price has a positive and significant effect on purchasing decisions, as indicated by a positive regression coefficient of 0.506 and a significance level of 0.000 < 0.05.